Genome-Wide Discovery of Single-Nucleotide Polymorphisms and Their Application in Population Genetic Studies in the Endangered Japanese Eel (Anguilla japonica) - Liu, Bing-Jian; Li, Yu-Long; Zhang, Bai-Dong; Liu, Jin-Xian (Frontiers in Marine Science, 2020)
The Japanese eel (Anguilla japonica) is a commercially important aquatic species in East Asia. The number of the Japanese eels has been dramatically declining over the last four decades, and it is now listed as an endangered species (International Union for Conservation of Nature [IUCN] 2014). To manage and conserve this endangered species, it is necessary to assess population genetic diversity, genetic structure, and identify regions of the genomes that are under selection. Here, we generated a catalog of novel single-nucleotide polymorphism (SNP) markers for the Japanese eel using restriction site-associated DNA (RAD) sequencing of 24 individuals from two geographic locations. The 73,557 identified SNPs were widely distributed across the draft genome of the Japanese eel. No genetic differentiation between the two populations was detected based on all loci or neutral loci. However, highly significant genetic differentiation was detected based on loci that appeared to be under selection. BLAST2GO annotations of the outlier SNPs yielded hits for 61 (72%) of 85 significant BLASTX matches. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified some of the putative targets of local selection, including genes in several important pathways such as calcium signaling pathway and intestinal immune network for IgA production. This SNP catalog will provide a valuable resource for future population genetic and genomic studies and allows for targeting specific genes and genomic regions under selection in the Japanese eel genome.